Relationship between client's perception of audit quality and audit fees. - Chua, An Chi. (2008)
This paper investigates the relationship between client's perception of audit quality and audit fees. The results of this study provide empirical evidence on whether client's perception of auditor reputation and client's satisfaction with the overall audit quality have any effect on audit fees.